Estimating Waves and Currents at the Saltmarsh Edge Using Acoustic Doppler Velocimeter Data - Liu, Bing; Chen, Yining; Cai, Tinglu; Li, Yan; Sun, Li (Frontiers in Marine Science, 2021)
Waves, currents, and related sediment transport are important factors driving the development of saltmarshes. Separating the effects of waves and currents accurately from simple field observations is a technical challenge in shallow water environments with limited inundation such as saltmarshes. In this paper, the estimation method of both wave and current information was studied mainly through the data obtained by a solely used field ADV (Acoustic Doppler Velocimeter, Vector). Phase and pressure inversion wave methods were both used to estimate wave parameters, which were then compared to synchronous observation by wave loggers at the front of a saltmarsh. Our results show that ADV is able to achieve simultaneous observations of tidal currents and waves independently. The pressure inversion wave method (r2 0.996) is more effective than the phase method (r2 0.876) in estimating wave energy when comparing with wave logger results. However, the former is more restricted by submergence depth and duration in field, while the latter provides cut-off frequencies for the pressure inversion wave method. Both methods can be combined to best estimate wave parameters from field ADV data. Further, hydrodynamic observation on a Scirpus mariqueter patch at the front of a saltmarsh was used as an application to indicate the importance of obtaining both wave and current information from field data. The patch was found to mainly reduce the advection of tidal currents, but it slightly increases wave energy. Therefore, it is necessary to consider the different effects of plants on tidal currents and waves simultaneously in field observations. This study confirms that ADV and associated analysis can detect waves and currents at reliable accuracy at the marsh edge, which is vital in assessing the long-term resilience of marshes to sea level rise and increased storm severity.